Lower retinal capillary density in minimal cognitive impairment among older Latinx adults. Issue 1 (25th August 2020) - Ashimatey, Bright S.; D'Orazio, Lina M.; Ma, Samantha J.; Jann, Kay; Jiang, Xuejuan; Lu, Hanzhang; Wang, Danny J.J.; Ringman, John M.; Kashani, Amir H.
Abstract: Introduction: We investigated the hypothesis that retinal capillary perfusion is a biomarker of early cognitive decline and cerebrovascular perfusion associated with small vessel disease in a pilot data set of Latinx adults at high risk for vascular cognitive impairment and dementia. Methods: High‐resolution optical coherence tomography angiography (OCTA) images were acquired from dilated eyes of Latinx subjects using a 3 × 3 mm 2 scan pattern from a commercially available device. A previously validated method was used to quantify the density of perfused retinal capillaries as the retinal vessel skeleton density (VSD). The association of VSD with Clinical Dementia Rating Sum of Boxes, total Montreal Cognitive Assessment (MoCA) score, and individual MoCA test elements were analyzed using multivariate statistics that adjusted for confounders. VSD was also compared with magnetic resonance imaging (MRI) measures of cerebrovascular reactivity (CVR) and perfusion in the middle cerebral artery perforator (MCA‐Perf) territory. Results: The mean (± SD) age of the subjects was 68 (± 6) years. For every 0.01‐unit lower VSD, the risk of having a CDR‐SOB >0 was 20% higher (95%CI = 5%–90%; P = .031). Similarly, a lower VSD was associated with lower total MoCA score (r = 0.3; P = .038). The Visuospatial/Executive domain of the MoCA assessment showed the strongest association with VSD ( β = 0.02; P = .022). Lower retinal VSD was associated with worse MRI measure of CVR (r = 0.7, P = .04) and less perfusion in the MCA‐Perf territory (r = 0.45, P = .02). Discussion: Impaired retinal capillary perfusion is associated with cognitive impairment and abnormalities in cerebrovascular perfusion and function. OCTA‐based retinal capillary assessment holds promise for identifying and quantifying retinal correlates of neurovascular abnormalities associated with vascular cognitive impairment.